A CONSTRUÇÃO CULTURAL DA NARRATIVA NOTICIOSA: noticiabilidade, representação simbólica e regularidade cotidiana - Silva, Marcos Paulo da (2013)
This dissertation is an eminently qualitative theoretical-conceptual discussion about the cultural construction of the newsworthiness criteria inside the journalism practice. Its central proposal is to insert the issue of newsworthiness that is, the debate around the responsible parameters for characterizing certain events as newsworthy events over others inside a wider cultural reflection that targets to dimensionate the news narrative as one of the most consistent elements of the modern everyday experience. The specific research goals are: 1) the theoretical discussion about some of the most significant conceptual approaches that the newsworthiness criteria have historically in the social sciences; 2) the presentation of an alternative group of theoretical conceptions that articulated can explain the complexity of the news selection process; and 3) a proposal of a theoretical-conceptual systematization for these articulations so that this dissertation could be synchronized with the state of art in the field of journalism theory. The debate will arrive, finally, in the creation of an explicative pendulum model that consolidates itself as a possible metaphor for the relation between the journalism practice, the everyday paradoxes and the symbolic parameters that characterize the everyday regularity as a cultural pattern of the modern sociability.